Scale-inhibiting coating composition, coating and preparation and application of scale-inhibiting coating composition

By using coating compositions composed of resin, hydrophobic nanosilicon dioxide and modified graphene in the hot water transportation and water flow metering industry, a scale-resistant coating with special structure and low surface energy is formed, which solves the scale problem and improves equipment efficiency and metrological accuracy.

CN119752321APending Publication Date: 2025-04-04DONGHUA UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411881727.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the hot water transportation and water flow metering industry, scale problems caused by hard heat medium water lead to crystallization, scale and floc precipitation on the surface of equipment and pipelines, affecting equipment efficiency and metrology accuracy, and increasing resource consumption and environmental pollution.

Method used

Using a coating composition, including resin, hydrophobic nanosilicon dioxide and modified graphene, the coating is obtained by ultrasonic and degassing treatment, loaded on the substrate surface and cured to form a scale-resistant coating with special structure and low surface energy.

Benefits of technology

This coating effectively delays the generation of scale crystals, improves binding force and wear resistance, is suitable for various pipes or instrument surfaces, significantly reduces the crystallization and generation of scale, and achieves a good scale resistance effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752321A_ABST
    Figure CN119752321A_ABST
Patent Text Reader

Abstract

The invention relates to a scale inhibition coating composition, a coating as well as preparation and application thereof, the scale inhibition coating composition has a good scale inhibition effect, the scaling problem is a big problem which puzzles the liquid transportation and metering industry all the time, scale generation on the surface of a base material is inhibited and slowed down by preparing a coating surface with a special microstructure and lower surface energy, and the scale inhibition effect is good. A good scale inhibition result is achieved through experimental tests.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional coatings, and particularly relates to an anti-scaling coating composition, a coating, and preparation and application thereof. Background Art

[0002] In the hot water transportation and some water flow metering industries, as the use time of equipment and some pipelines increases, the scale problem on the surface in contact with water has always been a major challenge faced by these industries. For hard heat medium water that has not been softened, it will gradually deposit on the surface of equipment and some pipelines or heat exchange equipment, and then produce crystallization, scaling and flocculent precipitation, which has a great impact on the use efficiency and metering accuracy of the equipment. At the same time, for some heat exchange equipment, the existence of scale further expands resource consumption and environmental pollution, which is not conducive to energy conservation and emission reduction and reducing carbon emissions. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide an anti-scaling coating composition, a coating and the preparation and application thereof.

[0004] The invention provides a coating composition, the components of which include resin, nano silicon dioxide and modified graphene.

[0005] Preferably, the resin is an organic silicone resin; wherein the organic silicone resin comprises polydimethylsiloxane (PDMS) resin;

[0006] Preferably, the nano-silica is hydrophobic nano-silica; further, the average particle size of the hydrophobic nano-silica is 20-30 nm.

[0007] Preferably, the nano-silicon dioxide accounts for 30-40% of the mass of the resin; the modified graphene accounts for 0-5% of the mass of the resin, and further, the modified graphene accounts for 0.5-5% of the mass of the resin.

[0008] Preferably, the modified graphene is a few-layer graphene modified material.

[0009] The method for preparing the few-layer graphene modified material comprises:

[0010] (1) mixing the few-layer graphene FLG, dopamine, KMnO4, and buffer, stirring, ultrasonically dispersing, and then standing for stratification and washing to obtain a precipitate;

[0011] (2) mixing the precipitate and the solvent, adjusting the pH value, adding fluorinated siloxane, and reacting to obtain a few-layer graphene modified material.

[0012] The buffer in step (1) is Tris buffer.

[0013] Preparation of the buffer in step (1): 10 mM Tris buffer is prepared with deionized water. The specific steps are: dissolving 0.24228 g of tris(hydroxymethyl)aminomethane in 200 ml of deionized water, stirring evenly to allow the solvent to fully dissolve, and adjusting the pH range of the buffer to 8-9 with acetic acid.

[0014] In the step (1), the few-layer graphene has 1-3 layers. The few-layer graphene is easy to prepare and has low cost compared to single-layer graphene. It also has good dispersibility and is beneficial to the grafting of compounds during the modification process. The buffer is a Tris buffer with a pH of 8-9.

[0015] Preferably, in step (1), the mass ratio of few-layer graphene, dopamine, and KMnO4 is 1:1:0.3 to 1:1:0.5;

[0016] Preferably, in step (1), the stirring speed is 500-700 r / min for 1.5-2 h; and the ultrasonic dispersion time is 15-30 min.

[0017] Preferably, in step (2), the solvent is ethanol; the fluorinated silicone is perfluorodecyltriethoxysilane; and the ratio of PFDTES to the solvent is 1 ml:40 ml to 1 ml:50 ml.

[0018] Preferably, in step (2), the pH value is adjusted to 2-4; and the reaction is carried out at 70-90° C. for 1-3 hours.

[0019] Furthermore, in the step (2), the precipitate and the solvent are mixed: the precipitate and the solvent are mixed and stirred for 10-20 minutes, and then ultrasonically treated for 5-10 minutes; and the pH value is adjusted by using acetic acid.

[0020] Furthermore, the few-layer graphene modified material obtained in step (2) is washed, dried to constant weight and then ground.

[0021] Preferably, the coating composition further comprises a curing agent and / or a solvent; wherein the solvent is a non-polar solvent, and n-hexane is used for dissolution; and the curing agent accounts for 5-15% of the mass of the resin.

[0022] The present invention provides a method for preparing a coating composition, comprising:

[0023] The resin, nano silicon dioxide, modified graphene and solvent are mixed and dissolved, a curing agent is added for dispersion, and then ultrasonication and degassing are performed to obtain a coating composition.

[0024] The ultrasonic time is 20-30 min; the degassing is vacuum degassing.

[0025] Furthermore, the preparation method of the coating composition includes: weighing each component, stirring and mixing the resin and the solvent, then adding the nano-silicon dioxide and stirring and dispersing, then adding the modified graphene and stirring and dispersing, adding the curing agent and stirring and dispersing, and vacuum degassing after ultrasonic vibration to obtain the coating.

[0026] The stirring time is 15-30 min.

[0027] The present invention provides an anti-scaling coating, which comprises any one of the coating compositions.

[0028] The invention provides a method for preparing a scale-inhibiting coating, comprising: loading a coating composition on a substrate surface and curing the coating composition, wherein the curing temperature is 60-200°C.

[0029] The substrate material is stainless steel or plastic and glass surface;

[0030] Furthermore, the curing temperature is 80°C-90°C for 2-3h.

[0031] Furthermore, the base material is a cleaned base material.

[0032] The present invention provides an application of any one of the coating compositions or the anti-scaling coating in the field of scale inhibition and scale suppression.

[0033] This coating uses the unique characteristics of the above two super-hydrophobic coatings and combines them with related modification methods to prepare a scale-inhibiting coating with a special structure and low surface energy. The coating preparation process is convenient and has little impact on the surface of the substrate. At the same time, the coating has a certain wear resistance and good bonding force, and can adapt to some extreme and harsh use environments.

[0034] Beneficial Effects

[0035] (1) The present invention effectively improves the bonding force and wear resistance of the coating by combining the modified nanofiller and the silicone resin, and the prepared coating is thin and uniform in thickness, with little impact on the surface of the substrate. At the same time, combined with the special structure and low surface energy, the formation of scale crystals is effectively delayed.

[0036] (2) The prepared coating has strong tolerance to the substrate surface and can be applied to various pipelines or instrument surfaces. It has little impact on the substrate surface and the formed coating has uniform thickness, which will not affect the functions of some liquid measuring instruments.

[0037] (3) The coating has a good scale inhibition effect. The scaling problem has always been a major problem plaguing the liquid transportation and metering industries. The present invention inhibits and slows down the scale formation on the substrate surface by preparing a coating surface with a special porous microstructure and low surface energy. The special porous structure can inhibit the crystallization and formation of scale. At the same time, uniform hydrophobic nanoparticles are dispersed around and inside the pores. After experimental testing, good scale inhibition results were achieved.

[0038] (4) The prepared coating has good bonding strength. After being enhanced by silicone resin and polydopamine, the coating can be stably attached to the surface of the substrate. The PDMS resin coating has the characteristics of good stability and corrosion resistance. Combined with the hydrophobic nanoparticles in this article, it can effectively play a scale inhibition effect.

[0039] (5) The coating preparation method is simple and does not require special preparation technology and processing methods. The manufacturing process will not cause harm to the environment, which is conducive to large-scale mass production and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the hydrophobic effect of graphene surface before (a) and after (b) modification;

[0041] Figure 2 This is the preparation process of GDF / SiO2 / PDMS composite coating, and a special microstructure is formed on the surface of the prepared coating;

[0042] Figure 3 The water contact angles measured for different amounts of GDF nanoparticles added;

[0043] Figure 4 This is the result of coating surface energy using non-polar liquid α-bromonaphthalene;

[0044] Figure 5 This is the scaling diagram of the coating surface after the structural experiment in the supersaturated calcium carbonate scaling solution for 6 hours and drying;

[0045] Figure 6 SEM images of the coating surface, where (a1), (a2), (a3) ​​are for adding 1% GDF nanoparticles; (b1), (b2), (b3) are for adding 3% GDF nanoparticles; (c1), (c2), (c3) are for adding 5% GDF nanoparticles;

[0046] Figure 7 This is the EDS spectrum result of the coating surface. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] Polydimethylsiloxane (Sylgard 184A): analytical grade, purchased from Dow Corning; curing agent (Sylgard 184B): analytical grade, purchased from Dow Corning; perfluorodecyl triethoxysilane (PFDTES): purity greater than 96%, purchased from McLean; hydrophobic nano-silica (average particle size 20nm), purchased from Foshan Blue Ridge Chemical Co., Ltd.; n-hexane: analytical grade, purchased from McLean; anhydrous ethanol: analytical grade, purchased from Guangdong Puhui Chemical Technology Co., Ltd.; few-layer graphene (average number of layers 3): purity 99%, purchased Acetic acid: analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd.; dopamine hydrochloride: purity greater than 98% purchased from McLean; potassium permanganate: purity greater than 99%, purchased from Shanghai Shangxi Weikang Pharmaceutical Products Co., Ltd.; tris (hydroxymethyl) aminomethane (Tris): analytical grade purchased from McLean; α-bromonaphthalene: analytical grade, purchased from Guangdong Wenglong Chemical Reagent Co., Ltd.; baking soda (NaHCO3) and calcium chloride (CaCl2) purchased from Sinopharm Chemical Reagent Co., Ltd. The experimental water was all deionized water, and the experimental temperature not specified in the experiment was carried out at room temperature 25°C.

[0049] Example 1

[0050] Preparation method of anti-scaling coating:

[0051] (1) Pretreatment of the stainless steel reflector: The surface of the reflector was polished smooth with 240 and 400 grit sandpaper to remove surface scratches and micro defects, then cleaned with acetone and anhydrous ethanol to remove surface grease, and finally ultrasonically cleaned in deionized water for 15 min and dried for later use.

[0052] (2) Modification of few-layer graphene (FLG)

[0053] ① Prepare 10 mM Tris buffer (0.24228 g tris(hydroxymethyl)aminomethane dissolved in 200 ml deionized water) with deionized water, and adjust the pH of the buffer to 8.5 with acetic acid.

[0054] ② Weigh 1g of few-layer graphene, 1g of PDA-HCl and 0.4g of KMnO4 and add them into the prepared 200ml Tris buffer, stir magnetically at 500r / min for 1h at room temperature, and ultrasonically disperse for 30min to activate and modify the graphene surface. The modified graphene surface has a large number of catechol groups, i.e., catechol structure, forming a dopamine coating layer.

[0055] ③ Let the modified graphene mixed liquid stand and separate into layers, and filter out the upper yellowish layer of liquid, retaining the lower filter mud.

[0056] ④ Use anhydrous ethanol and deionized water to wash alternately to remove unreacted impurities.

[0057] ⑤ Transfer the washed precipitate (FLG@PDA) to a beaker, add 20 ml of anhydrous ethanol, magnetically stir at 300 r / min for 20 min, ultrasonically treat at room temperature for 10 min, add acetic acid to adjust the pH to 3, add 0.5 ml of PFDTES (perfluorodecyltriethoxysilane), stir in an 80 ° C water bath for 2 h to complete the fluorination modification of graphene and reduce the surface energy of graphene.

[0058] ⑥ Repeat step ③ to wash the modified product. After washing, transfer it to an oven and dry it at 80°C to constant weight.

[0059] The dried product was preliminarily ground and transferred to a planetary ball mill for further grinding to obtain GPF (FLG@PDA-PFDTES) powder. The hydrophobic effect of the prepared powder is shown in the attached figure. Figure 1 shown.

[0060] like Figure 1 (a) shows a large amount of graphene adhering to the surface of a water droplet before modification; (b) is a schematic diagram of a water droplet on the surface after modification. After contact angle measurement, the modified graphene has a good hydrophobic effect.

[0061] (3)GDF / SiO 2 / Preparation of PDMS composite coating

[0062] ① Take 1g of polydimethylsiloxane (PDMS) resin in a beaker, add 10ml of n-hexane, and stir magnetically at 500r / min for 30min to fully dilute the resin material;

[0063] ② Add 0.4g of hydrophobic nano-silica and continue stirring for 30 minutes to completely disperse the nano-powder;

[0064] ③Add different doses of modified GDF powder particles (0, 10 mg, 20 mg, 30 mg, 40 mg, 50 mg) as samples 1-6, and continue stirring for 30 min;

[0065] ④ Add 0.1g PDMS curing agent and stir for 10 minutes to disperse completely;

[0066] ⑤ Ultrasonicate the mixed solution for 30 minutes and perform vacuum degassing to ensure a uniform coating solution and remove bubbles generated in the solution;

[0067] ⑥ Apply the treated solution dropwise on the sample surface and cure at 90℃ for 2h to obtain the prepared hydrophobic surface. The preparation process is as shown in the attached Figure 2 As shown. Figure 2 A special microstructure is formed on the surface of the coating after preparation.

[0068] Coating performance test

[0069] Hydrophobicity

[0070] The contact angle of the coating surface was measured using a JY-PHb contact angle meter. The specific operating steps were as follows: preliminarily clean the prepared coating to remove dust and other impurities on the surface to ensure that the coating was dry; fix the coating sample on the test bench, operate the test equipment to uniformly drip 10 μL of deionized water on the coating surface; use a high-power camera to take pictures of the drop state, use the tangent method to draw the baseline and left and right tangents, and calculate the water drop contact angle. The calculation results are shown in the attached figure. Figure 3 shown.

[0071] Surface energy

[0072] To calculate the surface energy of a solid using the Fowkes equation, it is necessary to measure the contact angle between the solid and the non-polar liquid. In this experiment, the non-polar liquid α-bromonaphthalene (London dispersion force is 44.6 mN / m) was used to calculate the surface energy of the coating. The results are shown in the attached figure. Figure 4 shown.

[0073] like Figure 4 As shown in the figure, the surface energy of the coating is measured using non-polar liquid α-bromonaphthalene. With the addition of GDF nanoparticles, the surface energy of the coating gradually decreases. The lower surface energy can effectively slow down the nucleation and growth of surface scaling ions, thereby achieving the effect of scale inhibition.

[0074] Bonding strength test

[0075] The coating adhesion test is carried out in accordance with ISO 2409-1992 standard, and the coating grade is judged according to the area of ​​the peeled area, as shown in Table 1. A 1mm (11-tooth) grating knife is used to uniformly cut the coating surface at a speed of 20-25mm / s. After the cutting is completed, the surface is lightly brushed with a soft brush. The 3M 600 test tape is used to completely cover the cut coating surface, and a 100g weight is used to roll on the surface at a uniform speed to make the test tape and the coating surface completely contact. The test tape is gently torn off at a small angle, and the ratio of the coating peeling area to the total area is observed and calculated, and the coating adhesion grade is evaluated. The results are shown in Table 2.

[0076] Table 1 Coating adhesion classification standards

[0077]

[0078]

[0079] Table 2

[0080]

[0081] From the comparison results, it can be found that with the increase of GDF nanoparticle content, the coating adhesion gradually increases. This is because the added modified particles contain polydopamine components. The surface of polydopamine contains rich amino and hydroxyl groups, which undergo secondary cross-linking reaction with the surface of the substrate, thereby improving the coating adhesion.

[0082] Anti-scaling performance

[0083] In order to test the anti-scaling performance of the prepared coating, a comparative experiment was conducted to quantify the specific scaling weight on the blank substrate and the coating surface. The specific test process is as follows:

[0084] ① Take 0.44g calcium chloride and 0.67g sodium bicarbonate and dissolve them in 500ml deionized water respectively. After complete dissolution, slowly merge the two solutions to form a saturated calcium carbonate scaling solution.

[0085] ② Prepare GDF / SiO2 / PDMS composite coatings with different content ratios respectively, and record the initial weight of the sample as m0

[0086] ③ Place the prepared coating at an angle in the prepared scaling solution, and conduct an accelerated scaling test at a water temperature of 80°C. Take out the sample every hour and dry it for 30 minutes, and record the sample weight m x (x is the experimental time).

[0087] ④ Calculate the sample weight change as m x -m0.

[0088] After calculation and testing, the scaling results of each sample are shown in Table 3.

[0089] Table 3

[0090]

[0091] With the increase of GPF nanoparticle content, the amount of scaling on the composite coating surface gradually decreased. When the content of GPF nanoparticles reached 5%, the scale inhibition rate of the coating reached 79.17%. By observing the surface of the sample dried after scaling for 6 hours, it can be found that when the content of GPF nanoparticles increased, the amount of scaling crystals generated on the surface was significantly reduced. Figure 5 It can be found that with the increase of the amount of GPF nanoparticles added, the number of scale crystals generated on the coating surface is significantly reduced, reflecting that the prepared coating has a significant inhibitory effect on the growth and deposition of scale crystals.

[0092] like Figure 6 The SEM images of the coating surface are shown, where (a1), (a2), (a3) ​​are added with 1% GDF nanoparticles; (b1), (b2), (b3) are added with 3% GDF nanoparticles; (c1), (c2), (c3) are added with 5% GDF nanoparticles. By comparison, it can be found that when the addition ratio is 3%, special microstructures in the form of holes appear on the coating surface. These structures can effectively store air and form a special "air layer", effectively reducing the contact area between the substrate and the liquid and slowing down the formation of scale. Moreover, as the content of nanoparticles added increases, the average diameter of the surface holes increases, which can store more air, corresponding to the above-mentioned contact angle measurement results.

[0093] like Figure 7 The EDS spectrum results of the coating surface are shown. It can be found that the C, O, Si and F elements on the surface are evenly distributed without large-scale agglomeration.

Claims

1. A coating composition, characterized in that The components of the coating composition include resin, nano silicon dioxide and modified graphene.

2. The coating composition according to claim 1, characterized in that: The resin is an organic silicone resin; wherein the organic silicone resin comprises polydimethylsiloxane (PDMS) resin; The nano-silica is hydrophobic nano-silica; The modified graphene is a few-layer graphene modified material; The nano silicon dioxide accounts for 30-40% of the mass of the resin; the modified graphene accounts for 0-5% of the mass of the resin.

3. The coating composition according to claim 2, characterized in that: The method for preparing the few-layer graphene modified material comprises: (1) mixing the few-layer graphene FLG, dopamine, KMnO4, and buffer, stirring, ultrasonically dispersing, and then standing for stratification and washing to obtain a precipitate; (2) mixing the precipitate and the solvent, adjusting the pH value, adding fluorinated siloxane, and reacting to obtain a few-layer graphene modified material.

4. The coating composition according to claim 3, characterized in that: In the step (1), the few-layer graphene has 1 to 3 layers of graphene; In the step (1), the mass ratio of the few-layer graphene, dopamine and KMnO4 is 1:1:0.3 to 1:1:0.5; In the step (1), the magnetic stirring speed is 500-700 r / min for 1.5-2 h; and the ultrasonic dispersion time is 15-30 min.

5. The coating composition according to claim 3, characterized in that: The fluorinated siloxane in step (2) is perfluorodecyltriethoxysilane PFDTES, with a molecular formula of C 16 H 19 F 17 O3Si; the ratio of PFDTES to solvent is 1ml:40ml~1ml:50ml; the pH value in the step (2) is adjusted to 2-4; the reaction temperature is 70-90°C, and the reaction time is 1-3h.

6. The coating composition according to claim 1, characterized in that: The coating composition further comprises a curing agent and / or a solvent; wherein the solvent is n-hexane; and the curing agent accounts for 5-15% of the mass of the resin.

7. A method for preparing a coating composition, comprising: The resin, nano silicon dioxide, modified graphene and solvent are mixed and dissolved, a curing agent is added for dispersion, and then ultrasonication and degassing are performed to obtain a coating composition.

8. A scale-inhibiting coating, characterized in that: The anti-scaling coating comprises the coating composition according to any one of claims 1-6.

9. A method for preparing a scale-inhibiting coating, comprising: The coating composition is loaded on the substrate surface and cured.

10. Use of the coating composition according to any one of claims 1 to 6 or the anti-scaling coating according to claim 8 in the field of scale inhibition and scale suppression.

Citation Information

Cited By

  • Preparation method and application of high-efficiency nano scale anti-fouling membrane

    CN122608206A